PREVALENCE AND EFFECTIVENESS OF DETECTING GASTROINTESTINAL DISORDERS ASSOCIATED WITH CHRONIC FATIGUE IN SEAMEN - Olexandr M. Ignatiev; Oleksij I. Paniuta; Tetiana L. Prutiian (Клінічна та профілактична медицина)
Aim. Chronic fatigue and fatigue-associated diseases restrict the active longevity and working capacity of seamen. By the age of 50, the most of seamen finish their career in marine fleet for medical or psychological reasons. The purpose of the work is to study the prevalence and effectiveness of detecting gastrointestinal disorders associated with chronic fatigue in seamen during pre-trip medical examinations.